GAMBARAN BUDAYA GENERASI MILENIAL DI KOTA SURABAYA DITINJAU DARI ENAM DIMENSI BUDAYA HOFSTEDE - Ikhwan Fadlu Fantazilu (Jurnal Adat dan Budaya Indonesia, 2022)
This study aims to determine how the cultural picture of the millennial generation in the city of Surabaya is viewed from the six dimensions of Hofstede's culture. This research is a quantitative research that uses the "VSM 08" questionnaire to collect the desired data. The sample of this study amounted to 100 subjects who were taken using accidental sampling technique. The data that has been collected is then analyzed using the formula that has been formulated by Hofstede. The results of the study detail that the millennial generation in the city of Surabaya which is reviewed through Hofstede's cultural dimensions has: (1) the Power Distance Index (PDI) has a high index with a result of 65.5 or believes there is a distance between power holders and those under them. (2) The Individualism Index (IDV) shows a low index score with a result of 13.5, which may indicate strong collectivism. (3) Masculinity Index (MAS) with a result of 64 or millennials in Surabaya City tend to like the pattern of competition. (4) The Uncertainty Avoidance Index (UAI) has a high index score of 79, meaning that millennials do not like things that are uncertain. (5) Long Term Orientation Index (LTO) has a result of 72.5 or happy future-oriented. (6) Indulgence Index (IVR) with a result of 46 or tend not to indulge in lust.